IMPACT OF PLANT SPACING ON THE GROWTH AND FRUIT YIELD OF WATERMELON VARIETIES IN SOUTH-WEST NIGERIA - Rihanat Funsho ASAFA; Wasiu Babatunde AKANBI; Abiola Elizabeth OJELEYE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Growth and yield of watermelon are significantly influenced by spacing and variety. To quantify these effects, field experiments were conducted from August to November 2016 in Ogbomoso and Sepeteri, Oyo State, Nigeria. The treatments consisted of four watermelon cultivars (Sugar baby, Kaolack, Grey belle and Collos F1) and five spacings (1.0 × 0.5 m, 1.0 × 0.75 m, 1.0 × 1.0 m, 1.0 × 1.5 m and 1.0 × 2.0 m). Data collection on reproductive and fruit yield attributes. Results showed that the growth parameters of the crop grown at Sepeteri were significantly better while those grown at Ogbomoso had higher fruit yield/yield parameters. In both locations, spacing significantly (p ≤ 0.05) influenced the fruit yield parameters for all the varieties. In Collos F1, vine line, number of secondary vines, leaves, flowers and rotten fruits were the highest while the number of fruits/plot and fruit yield (t/ha) were significantly higher in Kaolack cultivar. Spacing however had no significant influence on growth parameters but significantly affected number of fruits/plot and fruit yield/ha. In Ogbomoso, Kaolack sown at 1.0 x 0.75 m had highest fruit yield (41.7 t/ha) while the least (9.3 t/ha) was obtained from Sugar baby sown at 1.0 x 0.5m. Similarly, in Sepeteri, Kaolack sown at 1.0 x 0.75 m produced the highest fruit yield (19.4 t/ha) while the least (5.0 t/ha) was obtained from Collos F1 at 1.0 x 1.5 m. Planting Kaolack at spacing 1.0 x 0.75 m in both Ogbomoso and Sepeteri was the best agronomic practices for achieving the best fruit yield.